1999
DOI: 10.1002/(sici)1521-3862(199903)5:2<87::aid-cvde87>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A Single Source CVD Precursor to MgAl2O4: [Mg{(Ot-Bu)2AlH2}2]

Abstract: The hydride-modified heterometal alkoxide [Mg{(O t Bu) 2 AlH 2 } 2 ] (1), a precursor with tailored composition for single-source chemical vapor deposition (CVD) synthesis of MgAl 2 O 4 , has been synthesized and characterized using spectroscopic methods and single-crystal X-ray diffraction analysis. Thermal decomposition of 1, in a CVD process, on an inductively heated (450 C) metal substrate (steel, Ni, Cu) gave crystalline deposits of high purity MgAl 2 O 4 with low carbon contamination (<0.5 %) and nano-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…11,23,34,41,54,56 Low temperature synthetic routes can allow access to new phases or those with high dopant content, 12,30,59 and to materials that have high porosity and/or small particles sizes. 30,45,58,130 Examples demonstrate that synthesising CMOs from mixed-metal SSPs can improve their properties compared with those from mixtures of precursors. 43,44,46 Furthermore, many SSPs have good solubility, allowing for convenient processing and generating the potential for scale up of materials for practical applications using solution deposition techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,23,34,41,54,56 Low temperature synthetic routes can allow access to new phases or those with high dopant content, 12,30,59 and to materials that have high porosity and/or small particles sizes. 30,45,58,130 Examples demonstrate that synthesising CMOs from mixed-metal SSPs can improve their properties compared with those from mixtures of precursors. 43,44,46 Furthermore, many SSPs have good solubility, allowing for convenient processing and generating the potential for scale up of materials for practical applications using solution deposition techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Please do not adjust margins Please do not adjust margins least reduce the diffusion distances required to assemble the CMO structure. 32 By using lower synthesis temperatures, CMOs can be produced with small particle sizes and large surface areas, 30,45 or deposited onto more delicate substrates. The large amount of heat released from the decomposition of organic molecules can also facilitate the crystallisation of purephased oxides at relatively low reaction temperatures, enabling formation of high surface-area nanoporous structures otherwise unobtainable at higher temperatures.…”
Section: Opportunities Using Mixed-metal Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the unsolvated Mg compound [Mg{( t BuO) 2 AlH 2 } 2 ] has been reported previously, having a ion-paired dimeric molecular arrangement composed of Mg 2+ cations and [( t BuO) 2 AlH 2 ] − anions, 12 we anticipated a similar composition for 3 and 4. However, surprisingly the X-ray structures of both complexes revealed that their true nature is highly sensitive to the Lewis base ligand present.…”
Section: Aluminium Hydride Reagentsmentioning
confidence: 93%
“…Hydride metal alkoxides (homo and heterometal alkoxides) are attracting growing attention for their use to produce metal/ metal oxide thin films through chemical vapor deposition (CVD). [1,2] Further more, these compounds are versatile, as can be exemplified by the tert-butoxy alane, [H 2 Al(OtBu)] 2 : under CVD conditions at low temperatures the phase HAlO is formed, whereas with growing temperature either nano balls or nano wires of the biphasic composite Al/Al 2 O 3 are obtained. [2][3][4][5][6] The basic molecular structures of hydride/alkoxides of aluminum and gallium are often similar to that of metal alkoxides, varying from monomeric to polymeric.…”
Section: Introductionmentioning
confidence: 99%